Downcoast Redistribution of Changjiang Diluted Water Due To Typhoon Chan‐Hom (2015). Issue 4 (25th April 2023) - Lin, Yunpeng; Li, Yunhai; Cong, Shuai; Liu, Meng; Wang, Liang; Zheng, Binxin; Xu, Jingping
Abstract: Typhoons are known to substantially influence the coastal circulation and the associated biogeochemical processes. The transport of Changjiang diluted water (CDW), an important source to the coastal current in the East China Sea (ECS), varies markedly under the influence of typhoons. This study quantitively details the downcoast transport of CDW driven by Typhoon Chan‐Hom in the summer of 2015. Salinity measurements 3 days after the typhoon's passage showed the presence of a large volume of low‐salinity water, up to 70‐km wide and 20‐m thick along the Zhejiang‐Fujian coastal area with an estimated freshwater volume of 3.7 × 10 10 m 3 . A three‐endmember mixing model shows that the CDW's contribution to the study area's surface waters (<10 m) immediately after the typhoon was as high as 40% (average 32%), much greater than the contribution under normal summer conditions of 8% (average 3%). The vast spreading of CDW along the Zhejiang‐Fujian coast created a strong stratification in the upper water column that limited the diffusion of CDW in the study area. The calculated and observed results suggest that these abnormal low‐salinity water could stay in the study area for 13–21 days. Additional nutrients in the CDW elevated the Chlorophyll‐a concentration in the upper water column (mean 3.74 mg m −3 ) and produced large amount of particulate organic carbon. Plain Language Summary: In normal summer conditions, the Changjiang diluted water (CDW) mainly expands offshore to the northeast toward the Tsushima Strait. When typhoons strike the area, however, the downcoast transport of CDW was enhanced so much that its contribution to the water along Zhejiang‐Fujian coastal area grows 10‐fold from 3% to as much as 30%. These typhoon‐induced low‐salinity water float above the high‐salinity continental shelf water and can stay in the Zhejiang‐Fujian coastal area for 13–21 days. Nutrients brought by the CDW increase the primary productivity in the surface water with much higher concentration of Chlorophyll‐a and particulate organic carbon. Key Points: Typhoon Chan‐Hom caused an alongshore strip of low‐salinity water strip, up to 70‐km wide and 20‐m thick, along the Zhejiang‐Fujian coast Up to 40% (32% average) of this low‐salinity water strip was sourced from Changjiang diluted water (CDW) The long residence time (13–21 days) of this low‐salinity and eutrophic water elevated the Chlorophyll‐a concentration in the upper water column